Global Warming Potential of Nata de Coco Processing using Life Cycle Assessment Approach in CV. XYZ, Yogyakarta, Indonesia - Wahyu Supartono; Annisa Dwi Astari; Ratnadewi Widhiarti; Wahyu Windayanti; Ika Fajriah Gama Putri; Siti Fathonah Gama (Agroindustrial Journal, 2020)
Nata de coco is a well-known product in Indonesia which processed from coconut water. In the production process, the input of raw material and energy are needed to make nata de coco which the amounts are not small, as well as the amount of waste and emission which release to the environment. This study was conducted to find out how much the environmental impact in the process of making nata de coco using LCA methodology within the gate to gate scope. Analysis is carried out using functional unit on producing 1 kg of ready-to-sell nata de coco. This study was conducted by following the LCA methodology listed in ISO 14040-14043 series. The environmental impact caused by the production process of nata de coco is presented at midpoint level concentrated on global warming potential (GWP). The findings demonstrated that 0.285 kg of CO2-eq GWP were associated with 1 kg of nata de coco and firewood usage is the major contributes to the CO2 emissions.